Interoperability in Big, Open, and Linked Data--Organizational Maturity, Capabilities, and Data Portfolios. - Janssen, Marijn; Estevez, Elsa; Janowski, Tomasz (Computer (00189162), 2014)
Defining their data interoperability maturity level, expanding capabilities, and developing a data portfolio can help guide organizations as they move toward ubiquitous information sharing.